Preparation method and application of dimethyl ether carbonylation molding catalyst

By mixing the crushed molecular sieve waste into the molecular sieve, and the molded H-MOR molecular sieve catalyst is prepared by extrusion molding, the existing H-MOR catalyst has been solved, the strength and stability of the catalyst are improved, and it is suitable for dimethyl ether carbonylation reaction.

CN119633888APending Publication Date: 2025-03-18YANCHANG ZHONGKE (DALIAN) ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411722477.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing mordenite (H-MOR) has low catalytic activity and poor stability in dimethyl ether carbonylation reaction, which limits its promotion and application in the commercial field.

Method used

By crushing the molded molecular sieve waste to 80-150 mesh and mixing it into the molecular sieve, the molded H-MOR molecular sieve catalyst is prepared by extrusion molding method to increase the extrusion pressure and strength of the catalyst, and the crushed material is recovered.

Benefits of technology

In the reaction to carbonylation of dimethyl ether to methyl acetate, the strength of the catalyst is improved, the crushing rate is lower, the stability is also improved, and the catalyst activity remains unchanged.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005158539060000081
    Figure BDA0005158539060000081
  • Figure BDA0005158539060000091
    Figure BDA0005158539060000091
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a dimethyl ether carbonylation forming catalyst, and belongs to the field of industrial catalysis. The method comprises the following steps: S1, mixing Na-MOR molecular sieve raw powder, an adhesive and an extrusion aid, then adding acid, adding H-MOR molecular sieve catalyst waste, and carrying out mixing kneading, extrusion molding and drying to obtain a molded molecular sieve; s2, exchanging, drying and roasting the formed molecular sieve to obtain the formed H-MOR molecular sieve catalyst. According to the method, the formed molecular sieve waste is crushed to 80-150 meshes and then is mixed into the molecular sieve, so that the extrusion pressure can be increased, the strength of the formed catalyst is improved, and crushed aggregates can be recycled. In the reaction of preparing methyl acetate through carbonylation of dimethyl ether, under the condition that the activity of the catalyst is kept unchanged, the strength of the catalyst is improved, the stability is improved, and the crushing rate is lower.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a preparation method and application of a dimethyl ether carbonylation shaped catalyst, belonging to the field of industrial catalysis. Background Art

[0002] The basic characteristics of my country's natural resources are "rich in coal, poor in oil, and little gas", which determines that coal will dominate the primary energy consumption in the long term. The characteristics of my country's energy structure determine that the advantages of coal must be fully utilized. The preparation of ethanol from coal-based syngas, as an important part of ethanol production, is actively promoting the development of high-tech coal chemical industry and realizing the efficient and clean use of coal. It not only conforms to the characteristics of my country's energy structure, but also can alleviate the problem of insufficient oil supply in my country. This is of great strategic significance for ensuring my country's energy security, food security and alleviating air pollution.

[0003] Ethanol is an important chemical and a gasoline additive with excellent performance. Its large-scale production has long relied on biomass fermentation methods. With the increasing demand for fuel ethanol in my country, it is urgent to develop new ethanol production technologies. The technical route of using coal-based synthesis gas to produce methyl acetate through dimethyl ether carbonylation and then hydrogenating it to produce ethanol is in line with my country's resource structure characteristics of rich coal, poor oil and little gas. It is of great strategic significance to ensure national energy and food security and promote efficient coal conversion. Dimethyl ether carbonylation is the core process of this route. Although mordenite (H-MOR) shows certain activity in the dimethyl ether carbonylation reaction, it has problems such as low catalytic activity and poor stability, which restrict its promotion and application in the commercial field. Summary of the invention

[0004] According to the first aspect of the present application, a method for preparing a formed catalyst for dimethyl ether carbonylation is provided. The method crushes the formed molecular sieve waste to 80-150 meshes and mixes it into the molecular sieve, which can increase the extrusion pressure, improve the strength of the formed catalyst, and recover the crushed material without affecting the activity.

[0005] A method for preparing a dimethyl ether carbonylation formed catalyst, the method comprising the following steps:

[0006] S1, mixing Na-MOR molecular sieve raw powder, a binder, and an extrusion aid, then adding acid, adding H-MOR molecular sieve catalyst waste, kneading, extruding into strips, and drying to obtain a formed molecular sieve;

[0007] S2. exchanging, drying and calcining the formed molecular sieve to obtain a formed H-MOR molecular sieve catalyst.

[0008] Optionally, in step S1, the H-MOR molecular sieve catalyst waste is crushed to a mesh size of 80-150.

[0009] Optionally, in step S1, the mass ratio of Na-MOR molecular sieve raw powder, binder, extrusion aid, acid, and H-MOR molecular sieve catalyst waste is 100:10-40:1-5:30-60:10-30.

[0010] Optionally, in step S1, the acid is selected from at least one of nitric acid, hydrochloric acid, citric acid, oxalic acid, and malonic acid.

[0011] Optionally, the mass concentration of the acid is 5% to 20%.

[0012] Optionally, in step S1, the binder is selected from at least one of aluminum hydroxide, aluminum sol, and pseudo-boehmite.

[0013] Optionally, in step S1, the extrusion aid is selected from at least one of paraffin powder, methyl cellulose, starch, sesbania powder, and glucose.

[0014] Optionally, in step S1, the mixing time is 0.5 to 5 hours.

[0015] Optionally, in step S1, the kneading time is 0.5 to 5 hours.

[0016] Optionally, the molded H-MOR molecular sieve catalyst has a silicon-aluminum ratio of 5-50.

[0017] According to a second aspect of the present application, there is provided a use of a shaped H-MOR molecular sieve catalyst obtained by the method described above in carbonylation of dimethyl ether to produce methyl acetate.

[0018] The molded H-MOR molecular sieve catalyst obtained by the method described above is used in the carbonylation of dimethyl ether to produce methyl acetate.

[0019] The molded H-MOR molecular sieve catalyst prepared by the above method has improved catalyst strength and lower crushing rate while maintaining the same activity in the reaction of carbonylation of dimethyl ether to produce methyl acetate.

[0020] The beneficial effects of this application include:

[0021] The preparation method and application of the dimethyl ether carbonylation shaped catalyst provided in the present application have the effect of improving the strength of the shaped catalyst and recovering the broken materials. In the reaction of carbonylation of dimethyl ether to produce methyl acetate, the catalyst strength is improved, the broken materials rate is lower, and the stability is also improved while the catalyst activity remains unchanged. DETAILED DESCRIPTION

[0022] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0023] Unless otherwise specified, the raw materials and catalysts in the examples of this application were purchased through commercial channels.

[0024] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.

[0025] The silicon-aluminum ratio of H-MOR molecular sieve is 22.

[0026] In the examples, the concentration of the acid refers to the mass concentration.

[0027] The analysis method in the examples of this application is as follows:

[0028] Strength test of catalyst: The radial compressive strength of catalyst particles is measured according to the provisions of HG / T 2782, where the intelligent particle strength testing machine has a range of 0N-250N, the sample diameter is 3-3.5mm, the strip length is 3-5mm, both end surfaces are ground, and the number of particles measured in the sample is 40.

[0029] Product analysis: carried out on a Fuli GC9790 gas chromatograph, HP-PLOT / Q column, FID detector; dimethyl ether (DME) conversion rate and methyl acetate (MA) selectivity data were uniformly calculated by the area normalization method.

[0030] In the examples of this application, the conversion rate and selectivity are calculated as follows:

[0031] In the examples and comparative examples, the conversion of dimethyl ether (DME) and the selectivity of methyl acetate (MA) are calculated based on the carbon molar number of dimethyl ether:

[0032] Dimethyl ether conversion rate = [(molar number of dimethyl ether carbon in the feed gas) - (molar number of dimethyl ether carbon in the product)] ÷ (molar number of dimethyl ether carbon in the feed gas) × (100%);

[0033] Methyl acetate selectivity = (2 / 3) × (the number of moles of carbon of methyl acetate in the product) ÷ [(the number of moles of carbon of dimethyl ether in the feed gas) - (the number of moles of carbon of dimethyl ether in the product)] × (100%).

[0034] Crushing rate = crushing mass / (crushing mass + finished product mass).

[0035] Sources of waste:

[0036] 100g Na-MOR raw powder, 25g aluminum sol, 2g starch, mix for 1 hour, add 50g 15% HCl, knead for 1 hour, extrude into strips, and dry at 120°C for 6 hours to obtain a formed molecular sieve.

[0037] At 80°C, the formed molecular sieve and nitric acid solution were ion exchanged for 3 hours (the concentration of the nitric acid solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 600°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.

[0038] The formed H-MOR molecular sieve catalyst was sieved, and the crushed material sieved out by a vibrating screen (sieve mesh size 2.8 mm) was used as waste material, and the remaining catalyst was used as a finished catalyst.

[0039] Example 1

[0040] 100g Na-MOR raw powder, 25g aluminum sol, 2g starch, mix for 1 hour, add 50g 15% HCl, add 25g H-MOR molecular sieve catalyst waste (grinding mesh number 80-100), knead for 1 hour, extrude into strips, dry at 120℃ for 6 hours to obtain a formed molecular sieve.

[0041] At 80°C, the formed molecular sieve and nitric acid solution were ion exchanged for 3 hours (the concentration of the nitric acid solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 600°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.

[0042] Example 2

[0043] The operation is the same as in Example 1, except that only 18 g of H-MOR molecular sieve catalyst waste (crushed to a mesh size of 100-150) is added to obtain a formed molecular sieve.

[0044] At 80°C, the formed molecular sieve and sulfuric acid solution were ion exchanged for 3 hours (the concentration of sulfuric acid solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 550°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.

[0045] Example 3

[0046] The operation is the same as in Example 1, except that only 12.5 g of H-MOR molecular sieve catalyst waste (crushed to a mesh size of 80-100) is used to obtain a molded molecular sieve.

[0047] At 80°C, the formed molecular sieve and sulfuric acid solution were ion exchanged for 3 hours (the concentration of sulfuric acid solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 500°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.

[0048] Example 4

[0049] The operation is the same as in Example 1, except that only 25 g of H-MOR molecular sieve catalyst waste (crushed to a mesh size of 100-150) is used to obtain a molded molecular sieve.

[0050] At 80°C, the formed molecular sieve and ammonium sulfate solution were ion exchanged for 3 hours (the concentration of ammonium sulfate solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 600°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.

[0051] Example 5

[0052] The operation is the same as in Example 1, except that only 18 g of H-MOR molecular sieve catalyst waste (crushed to a mesh size of 80-100) is used to obtain a molded molecular sieve.

[0053] At 80°C, the formed molecular sieve and ammonium sulfate solution were ion exchanged for 3 hours (the concentration of ammonium sulfate solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 550°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.

[0054] Example 6

[0055] The operation is the same as in Example 1, except that only 20 g of H-MOR molecular sieve catalyst waste (crushed to a mesh size of 100-150) is added to obtain a formed molecular sieve.

[0056] At 80°C, the formed molecular sieve and sulfuric acid solution were ion exchanged for 3 hours (the concentration of sulfuric acid solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 500°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.

[0057] Comparative Example 1

[0058] 100g Na-MOR raw powder, 25g aluminum sol, 2g starch, mix for 1 hour, add 50g 15% HCl, knead for 1 hour, extrude into strips, and dry at 120°C for 6 hours to obtain a formed molecular sieve.

[0059] At 80°C, the formed molecular sieve and nitric acid solution were ion exchanged for 3 hours (the concentration of the nitric acid solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 600°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.

[0060] Comparative Example 2

[0061] The operation is the same as in Example 1, except that 25 g of H-MOR molecular sieve catalyst waste (crushed to a mesh size of 150-200) is added to obtain a formed molecular sieve.

[0062] At 80°C, the formed molecular sieve and sulfuric acid solution were ion exchanged for 3 hours (the concentration of sulfuric acid solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 600°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.

[0063] Comparative Example 3

[0064] The operation is the same as in Example 1, except that 20 g of H-MOR molecular sieve catalyst waste (crushed mesh size 60-80) is added to obtain a formed molecular sieve.

[0065] At 80°C, the formed molecular sieve and ammonium sulfate solution were ion exchanged for 3 hours (the concentration of ammonium sulfate solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 600°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.

[0066] Comparative Example 4

[0067] The operation is the same as in Example 1, except that 12.5 g of H-MOR molecular sieve catalyst waste (crushed to a mesh size of 150-200) is added to obtain a molded molecular sieve.

[0068] At 80°C, the formed molecular sieve and ammonium nitrate solution were ion exchanged for 3 hours (the concentration of the ammonium nitrate solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, the mixture was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 600°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.

[0069] Catalyst strength test:

[0070] The strength test of the molded H-MOR molecular sieve catalysts of the above-mentioned embodiments and comparative examples is carried out, as shown in Table 1, and it can be seen that the strength of the embodiments is significantly higher than that of the comparative examples. This shows that the extrusion molding method of the present application can significantly improve the strength of the catalyst. If the mechanical strength of the catalyst is not enough, there will be obvious wear and breakage, which may cause various problems in the operation of the industrial device. For example, the formation of fragments and fine particles may cause uneven distribution of fluid flow, blockage, and unacceptable high pressure drop, heat flow change, downstream fouling, etc. in the entire reactor. Therefore, improving the mechanical strength of the catalyst is crucial for the industrial application of the catalyst.

[0071] Table 1

[0072] Example / Comparative Example Average radial compressive strength of catalyst particles (N / cm) Example 1 108 Example 2 95 Example 3 88 Example 4 105 Example 5 98 Example 6 102 Comparative Example 1 65 Comparative Example 2 77 Comparative Example 3 58 Comparative Example 4 72

[0073] Breakage rate test:

[0074] The crushing rate of the molded H-MOR molecular sieve catalysts of the above examples and comparative examples was tested, as shown in Table 2, and it can be seen that the crushing rate of the examples is significantly lower than that of the comparative examples, indicating that the extrusion molding method of the present application can improve the output rate of the product.

[0075] Table 2

[0076] Example / Comparative Example Crushing rate Example 1 4% Example 2 6% Example 3 7% Example 4 5% Example 5 6% Example 6 5% Comparative Example 1 12% Comparative Example 2 11% Comparative Example 3 13% Comparative Example 4 12%

[0077] Evaluation of carbonylation of dimethyl ether to produce methyl acetate:

[0078] The H-MOR molecular sieve obtained in the above examples and comparative examples was used as a catalyst. The activity evaluation was carried out at a temperature of 188°C and a pressure of 2.0 MPa. The feed volume ratio DME:N2:CO was 1:13:7, and the volume space velocity was 1800 h -1 The operation was continued, and the reaction results were detected after 50 h and 200 h, as shown in Table 3.

[0079] Table 3

[0080]

[0081]

[0082] Note: MA selectivity is greater than 99%.

[0083] It can be seen from the above table that the DME conversion rate of the molded H-MOR molecular sieve catalyst prepared in the embodiment and the comparative example is not much different after running for 50 hours. After running for 200 hours, the DME conversion rate of the embodiment decreases slightly, while the DME conversion rate of the comparative example decreases significantly. It can be seen that the extrusion molding method of the present application can improve the stability of the catalyst.

[0084] In summary, the extrusion molding method of the present application can improve the strength of the molded catalyst and can also recover broken materials. In the reaction of carbonylation of dimethyl ether to produce methyl acetate, the catalytic strength is improved, the broken material rate is lower, and the stability is also improved while the catalyst activity remains unchanged.

[0085] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a dimethyl ether carbonylation catalyst, characterized in that: The method comprises the following steps: S1, mixing Na-MOR molecular sieve raw powder, a binder, and an extrusion aid, then adding acid, adding H-MOR molecular sieve catalyst waste, kneading, extruding into strips, and drying to obtain a formed molecular sieve; S2. exchanging, drying and calcining the formed molecular sieve to obtain a formed H-MOR molecular sieve catalyst.

2. The method according to claim 1, characterized in that In step S1, the H-MOR molecular sieve catalyst waste is crushed to a mesh size of 80-150.

3. The method according to claim 1, characterized in that In step S1, the mass ratio of Na-MOR molecular sieve raw powder, binder, extrusion aid, acid, and H-MOR molecular sieve catalyst waste is 100:10-40:1-5:30-60:10-30.

4. The method according to claim 1, characterized in that: In step S1, the acid is selected from at least one of nitric acid, hydrochloric acid, citric acid, oxalic acid, and malonic acid; The mass concentration of the acid is 5% to 20%.

5. The method according to claim 1, characterized in that In step S1, the binder is selected from at least one of aluminum hydroxide, aluminum sol, and pseudo-boehmite.

6. The method according to claim 1, characterized in that In step S1, the extrusion aid is selected from at least one of paraffin powder, methyl cellulose, starch, sesbania powder, and glucose.

7. The method according to claim 1, characterized in that In step S1, the mixing time is 0.5 to 5 hours.

8. The method according to claim 1, characterized in that In step S1, the kneading time is 0.5 to 5 hours.

9. The method according to claim 1, characterized in that: The molded H-MOR molecular sieve catalyst has a silicon-aluminum ratio of 5-50.

10. Use of the shaped H-MOR molecular sieve catalyst obtained by the method according to any one of claims 1 to 9 in the carbonylation of dimethyl ether to produce methyl acetate.